(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Banks today know better than anyone the opportunities and the risks they face in an ever-changing competitive environment. In offering e-commerce products, banks some key advantage over potential competitors. E-commerce would create opportunities for banks to strengthen their relationships with customers, sell additional services, and prevent encroachment on their business activities. Core banking is the services provided by a group of networked bank branches. Bank customers may access their funds and other simple transactions from any of the member branch offices.